Identification of Bacteria, Fungi, and Most Probable Coliform around Temporary Disposal Site at Gadang Village Banjarmasin - Farida Heriyani; Lia Yulia Budiarti; Nurlaili Rafina; Normaida Novianti; Puspa Astri Sella (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: Temporary Disposal Site (TDS) of Gadang Village Banjarmasin is one of the temporary landfills in Banjarmasin. The negative effects of waste can pollute the environment, including water and air. The purpose of this study was to identify airborne contaminant bacteria and fungi as well as the Most Probable Number (MPN) of Coliform value of piped water in the residential houses around Gadang TDS Banjarmasin. The research method is descriptive observational. The sample of this study were air and piped water. Air sampling is done by open plate and MPN Coliform sampling was obtained by purposive sampling method. The results of this study showed the air contaminant bacteria in the house were Staphylococcus aureus (55.56%) and Escherichia coli (44.44%) in the environment around the TDS all results were obtained with the same percentage. Aspergillus niger was dominantly found at a distance of 20-30 m and 40-50 m while Aspergillus flavus was mostly found at the distance around 30-40 m. MPN Coliform in piped water showed coliform bacteria contamination with MPN coliform index of 2.0-7.5/100ml water samples. In conclusion, Staphylococcus aureus bacteria is more common than Escherichia coli. Most fungi species found in this study was Aspergillus niger. In the piped water examination for all samples MPN Coliform was found in the low risk category. Keywords: Air contaminant bacteria, air contaminant fungi, piping water MPC coliform, Temporary Disposal Site